2022
DOI: 10.3389/fcvm.2022.924629
|View full text |Cite
|
Sign up to set email alerts
|

MiR-208b/miR-21 Promotes the Progression of Cardiac Fibrosis Through the Activation of the TGF-β1/Smad-3 Signaling Pathway: An in vitro and in vivo Study

Abstract: BackgroundRegulatory molecule microRNAs (miRNAs) have been implicated in myocardial fibrosis. However, the specific mechanism by which they lead to myocardial fibrosis remains unclear. This study aimed to explore the roles of miR-208b, miR-21 and transforming growth factor-β1 (TGF-β1)/Smad-3 signaling pathway components in cardiac fibrosis development.Materials and MethodsThirty-six consecutive acute myocardial infarction (AMI) patients were included in this study. Plasma was collected on admission and at 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…miR-208a expression levels are increased in conditions of oxidative stress, fibrosis, and inflammation after MI. An in vitro assay using H9c2 cells cultured under hypoxia showed that miR-208 and TGF-β levels increase with time during incubation, which is in line with similar findings in MI patients [ 133 , 181 ]. Additionally, in a healthy heart, miR-208a overexpression promotes the expression of endoglin, a membrane glycoprotein of the TGF-β receptor signaling pathway, whereas in an MI rat model, particularly high levels of this miRNA can be observed in the fibrotic area [ 182 ].…”
Section: The Emerging Impact Of Non-coding Rnas’ Regulation Of Cardia...supporting
confidence: 80%
See 1 more Smart Citation
“…miR-208a expression levels are increased in conditions of oxidative stress, fibrosis, and inflammation after MI. An in vitro assay using H9c2 cells cultured under hypoxia showed that miR-208 and TGF-β levels increase with time during incubation, which is in line with similar findings in MI patients [ 133 , 181 ]. Additionally, in a healthy heart, miR-208a overexpression promotes the expression of endoglin, a membrane glycoprotein of the TGF-β receptor signaling pathway, whereas in an MI rat model, particularly high levels of this miRNA can be observed in the fibrotic area [ 182 ].…”
Section: The Emerging Impact Of Non-coding Rnas’ Regulation Of Cardia...supporting
confidence: 80%
“…miR-21 also regulates other signaling pathways, such as pERK/ERK and Spry1/Erk/Map, with the latter contributing to fibrosis ( Figure 2 ) [ 131 , 132 ]. In H9c2 cells, the expression of TGF-β and miR-21 was increased, establishing that miR-21 promotes fibrosis by regulating TGF-β/Smad3 signaling [ 133 ]. Therefore, miR-21 has anti-inflammatory and pro-fibrotic roles because it participates in inflammation by inhibiting the p38 and NF-kB pathways, thus decreasing pro-inflammatory cytokine production, and in fibrosis by downregulating TGF-β pathway inhibitors ( Figure 2 ).…”
Section: The Emerging Impact Of Non-coding Rnas’ Regulation Of Cardia...mentioning
confidence: 99%
“…Some miRNAs promote the development of cardiac fibrosis, by activating the TGF-β/Smad signaling pathway. Zhang et al (2022a) verified that there was a positive correlation between miR-208b and miR-21 and the expressions of TGF-β1 and Smad3. The miR-208b/miR-21 promoted the development of cardiac fibrosis by activating the TGF-β1/Smad3 signaling pathway.…”
Section: Regulation Of Tgf-β/smad Signaling Pathway By Ncrnas In Card...mentioning
confidence: 73%
“…TGF-β1 is a stimulator which can convert cardiac fibroblasts to myofibroblasts. While classical TGF-β pathway signaling is mediated by the binding of TGF-β1 to transforming growth factor beta receptors II (TGFBR2) ( Huang et al, 2022 ), which subsequently phosphorylates and activates the Smad2 and Smad3, thereby promoting myofibroblast proliferation and migration, and leading to cardiac fibrosis ( Zhang et al, 2022a ). Non-coding RNAs (ncRNAs) can be broadly classified into microRNAs (miRNAs), long-stranded non-coding RNAs (lncRNAs), and circular RNAs (circRNAs) according to their functions ( Iu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these data, the authors concluded that these miRNAs could be used as potential biomarkers for AMI. Zhang et al [ 80 ] demonstrated that miR-21 and MiR-208b promote cardiac fibrosis in AMI patients, activating the TGF- β1/Smad-3 signaling pathway. Wang et al [ 44 ] investigated the role of miR-22 and miR-499 as sensitive biomarkers in the diagnosis of MI, confirming that these miRNAs could play an important role in early diagnosis.…”
Section: Resultsmentioning
confidence: 99%